Six polymorphisms in genes involved in DNA double-strand break repair and chromosome synapsis: association with male infertility. (18th June 2015) - Zhang, Xiaohui; Ding, Min; Ding, Xianping; Li, Tianjun; Chen, Honghan
Abstract: Four genes involved in DNA double-strand break repair and chromosome synapsis, i.e., testis expressed gene 11 ( TEX11 ), testis expressed gene 15 ( TEX15 ), mutL homolog 1 ( MLH1 ), and homolog 3 ( MLH3 ), play critical roles in genome integrity, meiotic recombination, and gametogenesis. We explored the possible association between single nucleotide polymorphisms (SNPs) in these genes and idiopathic male infertility involving azoospermia or oligozoospermia. A total of 614 fertile control and infertile men were recruited to this study in Sichuan, China. The latter group included 244 men with azoospermia and 72 men with oligozoospermia. Six SNPs in the TEX11, TEX15, MLH1, and MLH3 genes were investigated in both patients and controls by sequencing. The frequency distributions of SNPs rs6525433, rs175080, rs6525433–rs4844247, and rs1800734–rs175080 were found to be significantly different between patients and control groups ( p < 0.05), while rs4844247, rs323344, rs323346, and rs1800734 showed no significant difference between the two cohorts. Thus, the SNPs TEX11 rs6525433, MLH3 rs175080, rs6525433–rs4844247, and rs1800734–rs175080 might be associated with male infertility.